Slow food : the case for taste - Petrini, Carlo, 1949- (Arts and traditions of the table., 2003)
Slow Food is poised to revolutionize the way Americans shop for groceries, prepare and consume their meals, and think about food. The book not only recalls the origins, first steps, and international expansion of the movement from the perspective of its founder, it is also a powerful expression of the organization's goal of engendering social reform through the transformation of our attitudes about food and eating. As Newsweek described it, the Slow Food movement has now become the basis for an alternative to the American rat race, the inspiration for ""a kinder and gen.